Study on Blast Proof Composite Plate Structures - Ahmad Mohamed, Hassan; Abdolreza, Toudehdehghan (INTI International University, 2023)
Considering the remarkable growth in research activities and publications on blast-proof materials and structures in recent years, this article is trying to identify and highlight topics related to blast-proof structures and review representative papers that are related to the topics. A study of the research done in the domain of blast-proof structure and materials with an emphasis on recent works. Due to the wide development in blast-proof structures in the last decades, it is reasonable to cut down the study to a limited area by focusing on the blast-proof plate issues only. The study is related to deformation-fracture behavior, blast-loading, materials selection, and fabrication techniques of blast-proof. This study is planned to present the readers with a big-picture of studies and applications related to blast-proof. An attempt has been made here, to contain all the main portions in the blast-proof.